Brain glucodynamic variability is an essential feature of the metabolism–cognition relationship - Hamish A. Deery; Emma Liang; Chris Moran; Gary F. Egan; Sharna D. Jamadar (Proceedings of the National Academy of Sciences, 2026)
Variability ensures that complex biological systems, including the brain, are capable of responding to changing environmental demands. While the importance of neural variability in electrophysiological and hemodynamic aspects of brain activity is beginning to be understood, little is known about how variability in molecular activity influences brain function. Here, we examine how temporal variability in glucodynamics, or time-varying glucose use, is related to cognition in 35 younger and 43 older adults. Baseline metabolic rates of glucose indexed across the scan were not directly associated with cognition. Rather, higher glucodynamic variability, and its coherence into metabolic networks, was associated with better cognitive performance. Lower glucodynamic variability in aging was associated with altered metabolic network efficiency and reduced cognitive performance. Our results demonstrate for the first time that variability in cerebral glucose metabolism is biologically and functionally relevant to cognition and the network architecture of the brain. Cognition is influenced by time-varying glucose metabolism and its coherent fluctuations in metabolic networks. A loss of glucodynamics in aging reduces the efficiency of the metabolic connectome and contributes to reduced cognitive performance. The study of glucodynamics significantly advances our understanding of metabolic brain changes in health, aging, and disease.